Hearing aids in the elderly: quality of life and inequality - Filipa Morgado; Gonçalo Caetano; Andrea Gaspar; Luís Rodrigues; Constança Oom; Maria Machado; Alberto Santos; Carlos Macor (Revista Portuguesa Otorrinolaringologia e Cirurgia de Cabeça e Pescoço)
Objectives: To evaluate the impact of hearing aids (HA) on the quality of life of patients with presbycusis and identify the causes for not using them.